Characterization of alumina and spinel ceramic based inks for experimental investigation of inkjet printing for micro pattern generation on micro components - Yeo, Melvin Kiong Wei. (2009)
In this report, characterization studies were conducted with (a) alumina powder, (b) spinel powder, (c) alumina ceramic based inks of 10%, 20% and 30% volume concentration with fixed volume percentage of dispersant and (d) spinel ceramic based inks of 10%, 20% and 30% volume concentration with fixed volume percentage of dispersant. Observations on the characteristics of alumina and spinel powders were determined by optical microscopy (model: Axiotron 2 inspection microscope by HSEB) and scanning electron microscopy (model: S360 Convectional SEM system). It was observed that spinel powders were larger in size with irregularities. Observations on the dispersion rate of both alumina and spinel ceramic based inks of 10%, 20% and 30% volume concentrations were determined by scanning electron microscopy (model: S360 Convectional SEM system). It was observed that spinel ceramic based inks of 10%, 20% and 30% volume concentrations showed obvious and higher rate of agglomeration with poor dispersion rate. The viscosities of both alumina and spinel ceramic based inks of 10%, 20% and 30% volume concentrations were determined by a rotational rheometer by Anton Paar. It was observed that both alumina and spinel ceramic based inks of various volume concentrations showed shear thinning phenomenon and demonstrated the characteristics of as volume concentrations increase, viscosities increase. In addition, spinel ceramic based inks of various volume concentrations showed higher viscosities. Packing densities (Øm) of both alumina and spinel ceramic based inks of 10%, 20% and 30% volume concentrations were calculated. It was observed that as volume concentrations increase, packing densities increase. Measurements of contact angles were determined by an optical comparator (model: DH-216). It was observed that for alumina and spinel ceramic based inks of 10%, 20% and 30% volume concentrations, all the inks showed contact angles less than 90º (high wettability).